Standardization and contextualization: A study of language and leadership across 17 countries - UZUNÇARŞILI SOYDAŞ, AYDA (ELSEVIER SCIENCE INC, 2011)
With multinational corporations increasingly adopting English as a corporate language, the issue of language management and the pros and cons of language standardization have been widely debated in the literature. Our 17-country study considers whether the use of English as a common corporate language causes difficulties. We empirically examine whether managerial reactions to specific leadership scenario-based situations change as a consequence of the language they use. Our results show that the choice of language (native or English) does not matter much for the studied leadership scenarios. Instead, leadership decisions and reactions depend more on cultural and situational context. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Language; Leadership; Context; Culture; Multinational company; Cultural accommodation; ATTITUDE SCALE TRANSLATIONS; CULTURAL ACCOMMODATION; CHINESE BILINGUALS; ETHNIC AFFIRMATION; CROSS-LANGUAGE; HONG-KONG; COMPANIES; RESPONSES; VALUES